Lack of gene flow between Phytophthora infestans populations of two neighboring countries with the largest potato production - Wang, Yan‐Ping (Evol Appl, 2019)
Gene flow is an important evolutionary force that enables adaptive responses of plant pathogens in response to changes in the environment and plant disease management strategies. In this study, we made a direct inference concerning gene flow in the Irish famine pathogen Phytophthora infestans between two of its hosts (potato and tomato) as well as between China and India. This was done by comparing sequence characteristics of the eukaryotic translation elongation factor 1 alpha (eEF‐1α) gene, generated from 245 P. infestans isolates sampled from two countries and hosts. Consistent with previous results, we found that eEF‐1α gene was highly conserved and point mutation was the only mechanism generating any sequence variation. Higher genetic variation was found in the eEF‐1α sequences in the P. infestans populations sampled from tomato compared to those sampled from potato. We also found the P. infestans population from India displayed a higher genetic variation in the eEF‐1α sequences compared to China. No gene flow was detected between the pathogen populations from the two countries, which is possibly attributed to the geographic barrier caused by Himalaya Plateau and the minimum cross‐border trade of potato and tomato products. The implications of these results for a sustainable management of late blight diseases are discussed.